Pawn sacrifice [videorecording (DVD)] - Maguire, Tobey, 1975-; Sarsgaard, Peter; Schreiber, Liev (Bleeker Street Media, 2015)
In a gripping true story set during the height of the Cold War, American chess prodigy Bobby Fischer finds himself caught between two superpowers when he challenges the Soviet Empire. It chronicles Fischer's terrifying struggles with genius and madness, and the rise and fall of a kid from Brooklyn who captured the imagination of the world.